의료 빅데이터를 활용한 강원도 사망 원인 및 특성 분석 - 정대현(Dae-hyun Jeong); 권오영(O-young Kwon); 구영덕(Young-duk Koo) (한국콘텐츠학회 논문지, 18(9), 2018)
Due to the rapid development of medical information, vast amounts of medical data are accumulating, and such medical data is highly likely to be used as an important data for solving the aging population and the rapid rise in medical cost. Especially in Korea, there are resident registration numbers and computerized usage data for all citizens, so it can be superior to other countries in terms of medical infrastructure that can utilize big data. The purpose of this study was to analyze the factors affecting the mortality and death rate of Gangwon using the Big Data and the National Statistical Office data centered on Kangwon province. As a result of analysis, major variables related to the mortality rate of Gangwon were hospital infrastructure utilization rate, income level, aging population and population density. Therefore, inequalities due to income disparities and insufficient local medical infrastructures were affecting the local mortality rate, and policy support was needed to improve the local hospital infrastructure and income level. The results of this study were meaningful in that medical big data were used to analyze the deaths of people in Gangwon, and the causes of the deaths were analyzed through various social indicators and correlation analysis. 의료정보의 급속한 발달로 인하여 막대한 의료 빅데이터 정보가 축적되고 있다. 이러한 의료 빅데이터는 고령화와 의료비의 가파른 상승을 해결하는데 중요한 자료로 활용될 가능성이 큰 분야이다. 특히 한국의 경우 전 국민대상 주민등록번호와 전산화된 이용 자료들을 기반으로 빅데이터를 활용할 수 있는 의료 인프라 측면에서는 다른 국가에 비해 우위를 점할 수 있다. 본 연구에서는 국민건강보험공단 빅데이터 자료와 통계청 사망자 데이터를 활용하여 강원도의 사망자 분석 및 사망률에 영향을 미치는 요인을 분석하기 위해 상관분석을 수행한 후 시사점을 도출하였다. 분석 결과, 강원도 사망률과 관계된 주요 변수로는 자기지역 병원 인프라 이용률, 소득수준, 고령화 및 인구 밀도 등으로 나타났다. 따라서 소득격차에 따른 불평등과 지역 의료 인프라 부족 등은 지역의 사망률에 부정적 영향을 미치고 있는 것으로 나타나고 있어, 지역 병원 인프라 개선 및 소득 수준 향상을 위한 지역별 맞춤형 정책지원이 필요하다. 본 연구의 결과는 의료 빅데이터를 활용하여 강원도민 사망자를 분석하고, 다양한 사회 지표와 상관분석을 통해 그 원인을 파악해 보았다는 점에서 연구의 의의가 있다.